English curriculum analysis and its relevance to Islamic boarding school goals - Rina Lestari; Emi Emilia (Universitas Pendidikan Indonesia, 2023)
This case study reports on the analysis of the national curriculum known as curriculum 2013, and its relevance to a modern Islamic boarding school goals. This study involved one Islamic senior high school in West Java, Indonesia. The qualitative data were derived from curriculum 2013 and the curriculum complementary documents designed by the curriculum development department of the school. This document analysis relied on four fundamental elements of curriculum introduced by Tyler (1949), those are educational goals, learning experiences, learning organizations, and learning evaluations. The results showed that four fundamental aspects of the curriculum 2013 were in line with the Tyler curriculum principles. A minimum TOEFL score is one of the objectives, but the programs are inadequate to prepare the students to achieve it. Likewise, the final evaluation for the objective is still inconsistent due to the test cost issue. However, the curriculum 2013 supported by some complementary programs has demonstrated its relevance to the goals of the modern Islamic boarding school. Abstrak Studi kasus ini melaporkan analisis kurikulum nasional yang dikenal sebagai Kurikulum 2013, dan relevansinya dengan tujuan pesantren modern. Penelitian ini melibatkan salah satu SMA Islam di Jawa Barat, Indonesia. Data kualitatif diperoleh dari kurikulum 2013 dan dokumen pelengkap kurikulum yang dirancang oleh bagian pengembangan kurikulum sekolah. Analisis dokumen ini bersandar pada empat elemen dasar kurikulum yang diperkenalkan oleh Tyler (1949), yaitu tujuan pendidikan, pengalaman belajar, organisasi belajar, dan evaluasi belajar. Hasil penelitian menunjukkan bahwa empat aspek fundamental kurikulum 2013 sejalan dengan prinsip-prinsip kurikulum Tyler. Selain itu, sekolah memberikan lebih banyak tujuan dengan menambahkan persyaratan TOEFL. Skor TOEFL minimum adalah salah satu tujuannya, tetapi programnya tidak cukup untuk mempersiapkan siswa untuk mencapainya. Demikian pula, evaluasi akhir untuk tujuan tersebut masih tidak konsisten karena masalah biaya pengujian. Namun, kurikulum 2013 yang didukung oleh beberapa program pelengkap telah menunjukkan relevansinya dengan tujuan pesantren modern. Kata kunci: analisis Kurikulum 2013; Bahasa Inggris; pesantren modern; Tyler Rationale